A Rare Case of Fibrolamellar Hepatocellular Carcinoma with Unusual Presentation in a Young Indian Female- a case report - Nayak, Rashmi; Jain, Sharad (International Journal of Medical Research and Review, 2014)
Fibrolamellar carcinoma (FLC) is a rare subtype of Hepatocellular carcinoma (HCC) comprising Approx 1% of HCC. This variant of HCC commonly metastasizes to regional lymph nodes (celiac, gastric, para aortic). But metastasis to cervical lymph nodes is very rare. It is also very rare in Asian population. We are reporting a case of a rare cervical lymph node metastasis from FLC in an Indian female. Patient was a 20 yrs female presented with a cervical lymph node enlargement. USG and CT revealed lesion in liver and massive lymphadenopathy involving regional and para aortic group of lymph nodes. Diagnosis was made on histopathological examination of cervical lymph node biopsy.